Autoantibody profiles delineate distinct subsets of scleromyositis. (19th June 2021) - Leclair, Valérie; D'Aoust, Julie; Gyger, Geneviève; Landon-Cardinal, Océane; Meyer, Alain; O'Ferrall, Erin; Karamchandani, Jason; Massie, Rami; Ellezam, Benjamin; Satoh, Minoru; Troyanov, Yves; Fritzler, Marvin J; et al.
Abstract: Objective: Scleromyositis remains incompletely characterized owing in part to its heterogeneity. The purpose of this study was to explore the role of autoantibody profiles to define subsets of scleromyositis. Methods: Subjects with scleromyositis from a prospective cohort were divided into three groups based on autoantibody profiles: subjects with SSc-specific autoantibodies (anti-centromere, -topoisomerase 1, -RNA polymerase III, -Th/To, -fibrillarin), subjects with SSc-overlap autoantibodies (anti-PM/Scl, -U1RNP, -Ku) and subjects without SSc-related autoantibodies. Clinical features, laboratory tests and histopathological findings were retrieved and compared between groups. Results: Of 42 scleromyositis subjects (79% female, mean age at diagnosis 55 years, mean disease duration 3.5 years), 8 (19%) subjects had SSc-specific autoantibodies, 14 (33%) SSc-overlap autoantibodies and 20 (48%) had no SSc-related autoantibodies. One-third had no skin involvement, a finding more frequent in the SSc-overlap subjects and those without SSc-related autoantibodies. Proximal and distal weakness was common and head drop/bent spine was found in 50% of the SSc-specific and 35% of the subjects without SSc-related autoantibodies. Of note, the group without SSc-related autoantibodies had the only cases of severe cardiac systolic dysfunction ( n  = 1) and scleroderma renal crisis ( n  = 1), as well as three out of the four cancers and three out of the four deaths. Conclusion: In this carefully phenotyped series of scleromyositis subjects, absence of SSc-related autoantibodies was common and associated with distinct features and poor prognosis. Future studies are needed to validate these results and possibly identify novel autoantibodies or other biomarkers associated with scleromyositis.